2000
DOI: 10.1046/j.1469-8137.2000.00641.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in axial hydraulic conductivity along elongating leaf blades in relation to xylem maturation in tall fescue

Abstract: Xylem maturation in elongating leaf blades of tall fescue (Festuca arundinacea) was studied using staining and microcasting. Three distinctive regions were identified in the blade : (1) a basal region, in which elongation was occurring and protoxylem (PX) vessels were functioning throughout ; (2) a maturation region, in which elongation had stopped and narrow (NMX) and large (LMX) metaxylem vessels were beginning to function ; (3) a distal, mature region in which most of the longitudinal water movements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
59
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(69 citation statements)
references
References 50 publications
10
59
0
Order By: Relevance
“…The values of measured Kh were on average only 14-26% of theoretically predicted Kh values based on Hagen-Poiseuille equation for ideal capillary. Similar results were found also in other studies (Ewers et al 1989, Martre et al 2000. There are three main factors that contribute to this discrepancy.…”
Section: Discussionsupporting
confidence: 92%
“…The values of measured Kh were on average only 14-26% of theoretically predicted Kh values based on Hagen-Poiseuille equation for ideal capillary. Similar results were found also in other studies (Ewers et al 1989, Martre et al 2000. There are three main factors that contribute to this discrepancy.…”
Section: Discussionsupporting
confidence: 92%
“…Nonami & Boyer (1993) and Silk and colleagues (Silk & Wagner, 1980 ;Silk, 1994) have discussed the importance of such growth-sustaining water potentials. This interpretation seems consistent with some recent results of Martre et al (2000) who measured both water deposition rate and xylem radius through the growth zone of cultivated fescue leaves. They found that within a particular leaf the growth-associated water deposition rate was directly proportional to the local xylem radius throughout the growth zone.…”
Section: Comparison Of Anatomical Effects To Water Deposition Rates Isupporting
confidence: 93%
“…Indeed, mature tissues are located downstream of the growing zone, with a hydraulic connection that is not perfect because minor veins are still at a protoxylem stage (Martre et al, 2000). In addition, mature tissues have an appreciable capacitance, resulting in the relatively slow recovery of leaf water potential upon rehydration, while the xylem vessels have virtually no capacitance because they are rigid.…”
Section: A Transcriptome Analysis Suggests Possible Contributions Of mentioning
confidence: 99%